Reviving true essence of pluralistic value in Islamic city planning concept according to Medina Charter - San, Mya Su (2017)
When the greater part of Quran and Sunnah discuss how we could uplift the value of our being in every dimension, it is clear that Islamic guidance demands for the human excellence. Without a doubt, exemplary Islamic City is the goal we are aiming for. However in current times, very few countries such as that of Canada seems to be able to deal well with the different groups within a Nation where people of different background are favoured equally and even the newest member of the country is being welcomed by the community and given the same chances as the oldest member of the community despite of their background of ethnicity or religion. When communities around the globe have been struggling for cohesion and pluralism, this study attempts to analyse what are the Islamic values and solutions for the problem. However, there is a difference between ‘Tradition’ and the ‘Traditionalism’. If we do not recognize that factor, sometimes we end up failing to capture the real essence of a tradition. While trying to dig up the scripture and history, we need to be careful in not becoming the traditionalists by bringing ourselves back to live in 600 A.D. Therefore, we should propose to put forth a new modern constitution derived from authentic traditional origins that will honour each and every citizen’s private lives and under which they can enjoy the freedom to practice their faiths. The Medina Charter was prepared for the Medina City-State founded by Prophet Muhammad in 622 A.D. It was an agreement that was reached without war, fighting, violence, or compulsion; and all of its parties arrived at voluntarily due to their commitment to the shared principles. It is a Just Constitution which affirmed that everyone who was under its authority were cohesive, one, unified society with all of its citizens enjoying equal rights while having the same duties. But, despite its obvious importance, it has not gained much attention to be studied. The Objectives of the study are (i) To investigate the characteristics of Pluralism in Islamic City Planning (ii) To analyse the success of Medina Charter to a Pluralistic Islamic society (iii) To develop a framework on Pluralistic Islamic City. Transformative philosophical worldview will be adopted and a qualitative method will be implemented in this study with case study on Medina and the content analysis method on Medina Charter. The study will results to a recommendation of the most appropriate planning methods to improve a Pluralistic Islamic City. According to the analysis, any state’s pronouncement or policy which negate the pluralistic value is a threat in establishing a well-functioning State. We can contrive the findings into a framework of 5 major factors in shaping the Pluralistic Islamic City namely: Equality; Unity and Support; Fairness and Justice; Rights and Architecture. If these 5 categories were to be planned properly in accordance with the pluralistic values, we shall be able to revive the true essence of Islamic City.